Synthesis and microstructure of Pd/SiO2 nanosized particles by reverse micelle and sol-gel processing - Bae, DS; Han, KS; Adair, JH (ROYAL SOC CHEMISTRY, 2002)
Pd/SiO2 nanosized particles have been synthesized using a reverse micelle technique combined with metal alkoxide hydrolysis and condensation. The size of the particles and the thickness of the coating can be controlled by manipulating the relative rates of the hydrolysis and condensation reaction of tetraethyl orthosilicate (TEOS) within the microemulsion. The average size of synthesized Pd/SiO2 particles was in the size range 20-40 nm and Pd particles were 1-5 nm. The effects of synthesis parameters, such as the molar ratio of water to TEOS and the molar ratio of water to surfactant, are discussed.
Keywords: QUANTUM SIZE; COMPOSITE; CLUSTERS